1981
DOI: 10.1097/00006842-198108000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to the Tumor-Enhancing Effects of Stress

Abstract: Growth of P815 mastocytoma in syngeneic DBA/2J male mice was evaluated following several stress regimens. Although escapable shock did not enhance tumor growth, an equivalent amount of inescapable shock applied in a yoked paradigm markedly augmented tumor development. If mice received repeated stress sessions on 5-10 consecutive following tumor cell transplantation, the tumor-enhancing effects of an acute session were abrogated. This effect was not due to an antitumor effect exerted by a shock session applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Initial studies demonstrated whether implementation of different stress protocols (type and duration) would predict susceptibility to lung tumor development. Consistent with previous studies (Mazur-Kolecka B et al, 1994); (Sklar LS et al, 1981), varying intensity and duration resulted in distinct outcomes in tumor lesion formation as evident by a greater number of lung lesions that developed depending on the intensity and duration of stress exposure.…”
Section: Discussionsupporting
confidence: 90%
“…Initial studies demonstrated whether implementation of different stress protocols (type and duration) would predict susceptibility to lung tumor development. Consistent with previous studies (Mazur-Kolecka B et al, 1994); (Sklar LS et al, 1981), varying intensity and duration resulted in distinct outcomes in tumor lesion formation as evident by a greater number of lung lesions that developed depending on the intensity and duration of stress exposure.…”
Section: Discussionsupporting
confidence: 90%
“…From previous studies there is good reason to believe that the individual isolation would be a more severe stressor than confinement in groups 15 , 16 , 17 . However, the effect in this experiment would be chronic in nature, allowing for adaptation to occur, 18 , 19 , 20 , 21 even though isolation leads to separation anxiety in sheep 15 . This adaptation makes it very difficult to measure the level of stress at any particular time.…”
Section: Discussionmentioning
confidence: 78%
“…However, plasma cortisol concentration is not a good indicator of chronic stress, 6 , 22 , 24 , 25 , 26 , 27 as it measures the acute adrenal response around the time of blood sampling and the sheep's reaction to handling. The cortisol data showed that this response declined rapidly over successive sampling days in all groups, presumably due to habituation by the sheep to the sampling procedure 18 , 19 , 20 , 21 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Mice received a subcutaneous injection in the left flank region of 6.25 x 104 viable syngeneic P815 mastocytoma cells suspended in 0.25 ml of RPMI-1640 medium. This dose was selected on the bas;s of earlier results showing that this number of cells result-ed in tumor appearance (defined as 3 mm2) within 7 to 9 days in all animals (6). The P815 cells, which were acquired from a donor mouse bearing an ascites tumor, were washed twice in RPMI-1640 after being extracted and then suspended in this medium for injection.…”
mentioning
confidence: 99%